An optimal equilibrium for a reformulated Samuelson economic discrete time system - Maria Filomena Barros; Fernando Ortega (Journal of Economic Structures, 2019)
This paper studies the equilibrium of an extended case of the classical Samuelson's multiplier-accelerator model for national economy. This case has incorporated some kind of memory into the system. We assume that total consumption and private investment depend upon the national income values. Then, delayed difference equations of third order are employed to describe the model, while the respective solutions of third-order polynomial correspond to the typical observed business cycles of real economy. We focus on the case that the equilibrium is not unique and provide a method to obtain the optimal equilibrium.
Keywords: 330; Economic modelling; Samuelson model; Diference equations; Equilibrium; Optimal